SEC approves new municipal advisor fiduciary duty rule. Issue 2 (4th July 2016) - Wink, Stephen; Rienhardt, Anna; Ackerman, Brett M.; Miller, Sean
Abstract : Purpose: To analyze the Municipal Securities Rulemaking Board's new rule outlining the standards of conduct and fiduciary duties applicable to municipal advisors. Design/methodology/approach: This article contains a summary of new MSRB Rule G-42 and identifies key areas where the final version of MSRB Rule G-42 differs from the initial proposal. Findings: New MSRB Rule G-42 represents another significant milestone in the MSRB's development of a comprehensive regulatory framework for municipal advisors mandated under the Dodd-Frank Wall Street Reform and Consumer Protection Act and imposes significant requirements on municipal advisors. Originality/value: Practical guidance from experienced securities and financial services lawyers.